2015
DOI: 10.3345/kjp.2015.58.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of uropathogenicEscherichia coliisolated from Korean children with urinary tract infection

Abstract: PurposeWe investigated the molecular types of uropathogenic Escherichia coli (UPEC) by using conventional phylogrouping, multilocus sequence typing (MLST), and fimH genotyping.MethodsSamples of patients younger than 18 years of age were collected from the Chung-Ang University Hospital over 2 years. Conventional phylogenetic grouping for UPEC strains was performed by polymerase chain reaction (PCR). Bacterial strain sequence types (STs) were classified on the basis of the results of partial sequencing of seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
3
14
0
1
Order By: Relevance
“…The participants in our study had at least two of the following urologic symptoms; the most frequent complaint was dysuria followed by urine urgency, urine incontinence, flank pain, suprapubic pain, and a few with fever and chills. These findings are in agreement with results from studies conducted in South Korea [21] and Nigeria [24].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The participants in our study had at least two of the following urologic symptoms; the most frequent complaint was dysuria followed by urine urgency, urine incontinence, flank pain, suprapubic pain, and a few with fever and chills. These findings are in agreement with results from studies conducted in South Korea [21] and Nigeria [24].…”
Section: Discussionsupporting
confidence: 93%
“…No drug resistance was found to Meropenem and Imipenem, and this result has also been reported from South Korea [21], China [16]and Iran [28]. Low resistance was observed for Ciprofloxacin (14.5%), Nitrofurantoin (5%), Norfloxacin (15%) and Amikacin (2.5%) which is comparable to other studies in Ethiopia [7,29] and Iran [11,28].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The significant negative association with diarrhea for the yjaA gene reported in the study of Afset et al (6) and suggested that the presence of the yjaA gene may be a marker for low diarrheagenic potential aEPEC strains. The yjaA gene as the negative marker for diarrhea may be one possible reason for the association of B2 phylogenetic group with extraintestinal E. coli infections (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…последовательности праймеров, использованных в данной работе для амплификации фрагментов генов fimH, chuA, yjaA и участка днк TspE4.C2, описаны ранее в работе K.W. Yan et al [8], а последовательности праймеров для амплификации фрагментов генов pap, sfa, afa, iha, irp2, iuc, iroN, hlyA, vat, usp, set-1, kpsMT, iss, cva, ompT -в работе H. Momtaz et al [9]. при проведении пцр использовали 10-кратный пцр буфер б (зао «синтол», россия), 25 ммоль раствор днтФ (зао «синтол», россия), 25 ммоль раствор MgCl 2 (зао «синтол», россия), SynTaq днк-полимеразу (зао «синтол», россия).…”
unclassified